Tinjauan Hukum Pidana Islam Terhadap Anak sebagai Pelaku Bullying yang Menyebabkan Korban Meninggal Dunia - Nurjannah, Nurjannah (Mahesa Research Center, 2024)
This article aims to explain the phenomenon of bullying from the perspective of Islamic criminal law, specifically focusing on the perpetrators of bullying that caused the death of the victim according to Islamic law. This research approaches the issue using normative legal research methods and literature review. The research method is further detailed to include data collection through legal analysis of relevant laws and scientific literature on bullying. The results concluded that bullying is a prohibited act, which results in physical and mental harm to the victim. In the context of Islamic criminal law, sanctions for bullying differ between adult perpetrators and minors. Adult perpetrators who cause injury, loss, or death to the victim may be subject to severe penalties such as hudud, qishash, and ta'zir. In contrast, if bullying is committed by minors, they may be subject to ta'zir punishments, including diyath, kaffarah, alternative or substitute punishments ('uqubÃ¢t al-badilÃ¢h), which aim to educate and deter the perpetrators and others from repeating similar acts. This comprehensive approach to research methodology provides a deeper understanding of the validity of the findings in the context of Islamic jurisprudence.